Implementation of Sharia Economic Principles in the Management of Waste Bank Savings to Empower Customers of the IAI MU Tanjungpinang Waste Bank - Sirly Deska Yana Putri; Masjunaidi Masjunaidi; Mardhiah Mardhiah; Muhammad Imaduddin; Novi Suryawati; Rida Salasa; Selly Anggreni (Transpublika Publisher, 2025)
Waste management remains a critical global challenge, with innovative solutions like waste banks gaining traction as participatory approaches to address environmental and economic concerns. However, conventional waste bank models often overlook the integration of spiritual and ethical values in their operations. This research aims to analyze the implementation of Islamic economic principles in waste-based savings management at IAI Miftahul Ulum Tanjungpinang Waste Bank and its role in customer empowerment. The research uses descriptive qualitative methods with data collection techniques through interviews, observation, and documentation. The research subjects are Bank Sampah customers with 22 active customers depositing every 1 and 2 weeks. The informants in this research are the director and staff at IAI MU Tanjungpinang Waste Bank. Customer empowerment at IAI Miftahul Ulum Tanjungpinang Waste Bank is implemented through three main aspects: economic, social, and spiritual. These activities are supported by the existence of educational institutions, initial community awareness, strategic location, and potential religious values. However, the implementation of customer empowerment in these three aspects has not been optimaldue to limitations in operational time, unavailability of recycling programs, weak integration of spiritual values in activities, and minimal non-economic incentives. As a result, the impact of empowerment on improving welfare and customer awareness remains limited, requiring program strengthening and sustainable innovation.